PERANCANGAN SISTEM INFORMASI ABSENSI DAN KEGIATAN PESERTA MAGANG PADA TELKOM AKSES PADANGSIDEMPUAN - Lutami, Bunga Adelia (Jurnal Sistem Informasi (JUSIN), 2024)
Attendance is a crucial method for tracking whether individuals are present at specific activities. In today's era, technology-based attendance systems are widely used because they provide convenience and efficiency. However, TELKOM AKSES PADANGSIDEMPUAN still relies on manual processes for recording attendance and tracking intern activities. This manual approach often leads to inaccuracies and issues with discipline. To address these challenges, an Attendance and Activity Information System for Apprentices was developed for the Telkom Padangsidempuan Office. The system's design involved several stages, including interviews, data collection, and observational data analysis. Additionally, UML (Unified Modeling Language) was employed to design and analyze each component of the system. This technology-based solution aims to enhance the accuracy of attendance records and improve overall discipline, providing a modern and efficient alternative to traditional manual methods